Analisa Kelayakan Usaha Budidaya Udang Vannamei (Litopenaeus Vannamei) Tambak Semi Intensif dan Intensif di Desa Dampyak, Kecamatan Kramat, Kabupaten Tegal - Fatkhur Rafi Darmasnyah; Suyono Suyono; Nurjanah Nurjanah (Asosiasi Riset Ilmu Tanaman dan Hewan Indonesia, 2026)
This study aims to analyze the feasibility of vannamei shrimp farming in Kramat District, Tegal Regency. The research was conducted on several shrimp ponds using semi-intensive and intensive systems. The analysis includes calculations of investment costs, fixed and variable costs, revenues, income, and business feasibility indicators such as R/C Ratio, Payback Period, Break Even Point (BEP), Net Present Value (NPV), and Internal Rate of Return (IRR). The results show that vannamei shrimp farming is feasible, as indicated by an average R/C Ratio of 1.68 and a Payback Period of 1.90. All ponds yielded positive NPV values, with an average of IDR 546,070,598 and an IRR of 58%, which exceeds the 5.5% discount rate. Both price and production BEP values have been surpassed in all farming units. The intensive pond system proved to be more profitable than the semi-intensive system. Therefore, vannamei shrimp farming in Kramat District, particularly in Dampyak Village, has strong financial prospects and is feasible for development through intensive approaches and the application of modern technology.